HIV/AIDS em Mato Grosso do Sul: análise de tendência, distribuição espacial e sobrevida dos casos - Werle, Josiel Elisandro (2021)
The HIV/AIDS pandemic expands exponentially throughout the world, presents a constant change in the epidemiological profile, which generates the need for studies that identify and characterize the factors that contribute to its prevention and control. Thus, the present study aims to analyze the trend, spatial distribution and survival of HIV/AIDS cases in the state of Mato Grosso do Sul. This is an ecological, analytical study, carried out based on the notifications of HIV/AIDS cases in the state of Mato Grosso do Sul in the period 2009-2018. Data were collected in December 2019 from a database made available by the State Department of Health. Subsequently, they were submitted to descriptive and analytical statistical analysis through the analysis with application of polynomial regression and geospatialization of the cases. Survival analysis was used by the Kaplan-Meier method and cox model to verify the existence of associated factors. The project was previously submitted and approved by the Ethics Committee on Research with Human Beings of UFMS under opinion no. 3,789,678. 734 notifications were recorded in the border region, when 57.9% of the cases were in men and with a higher incidence in the biennium 2017-2018 in both sexes. The trend of growth of notifications showed positive acceleration in twin cities (r2=0.91; p<0.001). The highest coefficients of determination were observed in women aged 35 to 49 years (r2=0.98; p<0.001) and in men aged 15 to 19 years (r2=0.96; p<0.002). In the state, 9,157 HIV/AIDS notifications were found in the period analyzed, with a progressive increase over the years. The total trend was increasing for both sexes (p<0.001, r2=0.94, both). The Municipal Human Development Index was related to the highest number of cases (Municipality of notification p=0.01 and municipality of residence p=0.02), when the highest concentration occurred in the host cities of the macroregions. For survival analysis, 8,712 notifications were considered, whose age group of 20-34 years concentrated 44.84% of the records, female gender and injecting drug use had a higher risk of death. The HIV/AIDS epidemic is present in the state of Mato Grosso do Sul, with the advance of new cases with a process of pauperization and feminization of cases. However, the increase in life time after diagnosis demonstrates an improvement due to interventions performed with this population. This study is expected to provide support for further investigations addressing quality of life and clinical conditions, as well as public strategies for improvements in health care.